Suspect saints and holy heretics: disputed sanctity and communal identity in late medieval Italy - Peterson, Janine Larmon (Cornell University Press, 2019)
"This book explores cases of disputed sanctity in thirteenth- and fourteenth-century Italy, examining how local communities used saints' cults as a tool to challenge papal authority"--